A Study of Agricultural Buffers and Rural-Urban Fringes: A Case Study of Deh 202 Taluka, Jhuddo District, Mirpurkhas - Fatima, Mutiba; Mushtaque, Daniyal (Journal of Environmental Science and Engineering Technology, 2025)
The semi-arid areas like Mirpurkhas experience growing environmental pressure because of the loss of vegetation, heat stress, and the growing settlement patterns in rural-urban fringe areas. Agricultural buffers like tree belts, grass waterways, and wetland strips are globally known to enhance microclimates, lower soil erosion, and improve landscape quality. The study explores the perception of six forms of agricultural buffers and three levels of buffer intensity by the stakeholders in the rural-urban fringe of Deh 202, Taluka Jhuddo, District Mirpurkhas. Farmers, residents, and academics were surveyed using a photo-questionnaire survey. A 5-point Likert scale was used to assess six types of buffers and three conditions of the buffers (no buffer, basic buffer, and extensive buffer). The findings showed that there were no statistically significant differences in the stakeholder groups in any type of buffer or condition (all p > .05). Descriptive trends indicated a strong preference hierarchy, with the Riparian tree buffers receiving the strongest approval across stakeholder groups. And then the grass waterways, riparian grass strips, wetland buffers, odor buffers, and windbreaks. Although the differences between the groups were not significant, the stakeholders showed a strong inclination towards dense tree-based buffers, which is both a global trend and a response to local climatic requirements. The planned strategies can focus on tree-dominant buffer designs, which are subject to uniform patterns of stakeholder preferences as observed in this study.